THE VISION OF THE PARENTS ON THE "PROGRAMA SEGUNDO TEMPO": ANALYSIS OF TWO COMMUNITIES OF THE CITY OF PELOTAS/RS (Fiep Bulletin - online, 2014)
This research has as objective analyzes a public politics of the federal government, proposal and implemented by the Ministry of the Sport, to be developed at the schools and in the communities in the inverse shift of the students' regular study, entitled "Programa Segundo Tempo". In this article some are presented data of the study regarding the parents' perception about the children's participation in the "Programa Segundo Tempo" in the two investigated communities: Piracema and Botucatu. The adopted methodology was based in the qualitative approach. The interest in accomplishing this research is arrested to the importance of the evaluation of public politics that serve as reference for new projects, given the limited actions in the section of sports and of leisure. The relevance of that analysis type is in its possibility of serving as subsidy for the definition of actions of public politics for the section. This study demonstrated that for the parents the "Programa Segundo Tempo" was a quite significant action, since it constituted access possibility at the same time to sport activities and leisure and the children's of the "street" removal. Away with this meaning for the participants of the program, it can be inferred that actions of that nature cannot be dependent of the rulers' political will, that check larger or smaller space in their government programs the those activities.
Keywords: public politics; parents; sport